2015
DOI: 10.1590/s1677-5538.ibju.2015.02.24
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of monotherapy prostate brachytherapy in patients with prostate cancer. Initial PSA and Gleason are important for recurrence?

Abstract: Purpose To evaluate the clinical outcome of a cohort of localized prostate cancer patients treate with 125-I permanent brachytherapy at the São José Hospital – CHLC, Lisbon.Materials and Methods A retrospective analysis was carried out on 429 patients with low and intermediate-risk of prostate adenocarcinoma, according to the recommendations of the EORTC, who underwent 125I brachytherapies in intraoperative dosimetry “real-time” system between September 2003 and September 2013.Results The mean follow-up was 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, a Portuguese single-centre retrospective study ( 31 ) was identified that reported 6-year real-world outcomes in non-high-risk LPC [defined according to European Organisation for Research and Treatment of Cancer ( 32 )] between 2003 and 2013; however, in this previous study, the patients were only treated with brachytherapy, and therefore it cannot be used for comparing outcomes or treatment patterns with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a Portuguese single-centre retrospective study ( 31 ) was identified that reported 6-year real-world outcomes in non-high-risk LPC [defined according to European Organisation for Research and Treatment of Cancer ( 32 )] between 2003 and 2013; however, in this previous study, the patients were only treated with brachytherapy, and therefore it cannot be used for comparing outcomes or treatment patterns with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Parra et al in Spain reported that GS 8 was the main score with the ability to predict independently the OS of the patients with a statistical significance (푝 = 0.006) [30]. Galego et al in Portugal reported a correlation between 5-year OS and GS (푝 < 0.05) [31]. In their study they also found that GS 7 was an independent predictor of the biochemical relapse of the disease unlike PSA.…”
Section: Correlation Of Gleason Score (Gs) With 3-year Overallmentioning
confidence: 89%
“…In their study they also found that GS 7 was an independent predictor of the biochemical relapse of the disease unlike PSA. Early detection of PCa is usually linked with low stage at diagnosis as well as low tumour grade [31,32]. For countries where screening of PCa is massive and sustainable, it has been found that most of the patients are diagnosed at early stage and for that matter they have low tumour grade which is usually determined by GS [33].…”
Section: Correlation Of Gleason Score (Gs) With 3-year Overallmentioning
confidence: 99%
“…Nowadays, interstitial implantation of 125 I seeds has been used to treat prostate cancer, and some other forms of recurrent or inoperable malignancies, such as non-small cell lung cancer, pancreatic cancer, and intracranial gliomas. [4][5][6][7][8] Previously, Ren et al 3 reported the use of 125 I seeds placed into the resected tumor bed of a patient with recurrent lumbar vertebral chondrosarcoma who underwent marginal resection. Although the pathology specimen was showed conventional low-grade chondrosarcoma, the treatment was effective, with no signs of recurrence at the 2-year follow-up.…”
Section: Introductionmentioning
confidence: 99%